Osobennosti podgotovki sportsmenok v skorostno-silovych vidach legkoj atletiki - Vrublevskij, E. P. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The purpose of the research was to develop and prove the criteria of estimations of speed-power abilities of female athletes and the basic directions of an individualization of process of their training in the view of features of a female organism.